Evaluasi Efisiensi Sistem Kearsipan Elektronik dalam Pengelolaan Arsip Dinamis: Studi Kasus Pada Aplikasi SRIKANDI di Institusi Pemerintah - Arnetta Fairuz Azzahra; Nandang Alamsah Deliarnoor; Andi Kasman (Dinasti Research, 2025)
This study aims to analyze the efficiency of the SRIKANDI application in managing dynamic archives in government agencies. The method used is a quantitative survey by distributing questionnaires to 100 respondents consisting of employees at various levels of office. The results of the study showed that the majority of respondents (70%) use the SRIKANDI application every day, with a high level of user satisfaction, namely 85% feeling satisfied and very satisfied. The efficiency of archive management is considered good, with an average score above 4.0 for aspects of access speed, storage space savings, and ease of collaboration. However, this study also identified several obstacles, including technical problems and lack of adequate training, with an average obstacle score reaching 3.8. These findings indicate that the SRIKANDI application plays an important role in improving the efficiency of archive management, although there is a need for improvement in terms of technical support and human resource training. This study is expected to provide recommendations for further development of the SRIKANDI application and improve the quality of archive management in government agencies.